BINARY VECTOR CONSTRUCTION OF KAPPA(κ)-CARRAGEENASE GENE AND TRANSFORMATION TO Agrobacterium tumefaciens AS MEDIATOR FOR SEAWEED TRANSGENIC GENERATION - Muh Alias L. Rajamuddin; . Alimuddin; Utut Widyastuti; Enang Harris; Emma Suryati (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Increasing of kappa (κ)-carrageenan content in Kappaphycus alvarezii seaweed is potentially be achieved by applying transgenesis technology. This study was performed to obtain a construction of  κ-Carrageenase gene and Agrobacterium tumefaciens to carry those construction genes.  The κ-Carrageenase (κ-Car) gene was involved in κ-carrageenan biosynthesis. The κ-Car gene sequence was ligated between the 35S CaMV promoter and tNos terminator sequences to generate pMSH/κ-Car expression vector. Transformation of pMSH/κ-Car plasmid to Escherichia coli was performed by heat-shock method, and to Agrobacterium tumefaciens by tri-parental mating method. The results showed that several colonies of E. coli and A. tumefaciens grew in the selective culture mediums containing antibiotic. PCR analysis using primers 35S-Forward and tNos-Reverse with DNA template from those bacterial colonies resulted DNA fragment of about 2,000 bp, the same as the total length of 35S CaMV promoter, κ-Car gene and tNos terminator sequences. Therefore, the construction of pMSH/κ-Car gene was succeeded and a colony of A. tumefaciens transformant carrying pMSH/κ-Car plasmid was successfully produced.                                                                                   Keywords:  Agrobacterium tumefaciens, kappa(κ)-Carrageenase gene, transgenesis, vector